Knowledge on Post Exposure Prophylaxis of HIV among Nurses of a Private Hospital - Khadgi, Deepika; Shah, Pooja; Mahato, Anju; Khadgi, Karishma (Birat Journal of Health Sciences, 2022)
Introduction: There are many effective prevention interventions available for those experiencing occupational exposure, and post exposure prophylaxis (PEP) is one of them. Different studies worldwide have shown low utilization of PEP for HIV due to lack of adequate knowledge. Objective: The purpose of this study was to assess the knowledge on PEP of HIV among nurses. Methodology: Descriptive cross-sectional research design was used and all the 130 nurses working in a private hospital of Biratnagar were the sample. Self-administered semi-structured questionnaire was used. Descriptive statistics as percentage, mean, median and standard deviation were used to analyse the data. Results: Almost all of the nurses knew the meaning of PEP and the majority were aware about components, indications and best time for initiating PEP after exposure. Less than half had knowledge about appropriate treatment regimen, antiretroviral drugs used for PEP, PEP drugs contraindicated during pregnancy, effectiveness of PEP and duration of protection by PEP. Findings also revealed that only one-third of the nurses (35.8%) had adequate knowledge on PEP of HIV. Conclusion: In least developed and developing countries like Nepal, healthcare workers including nurses have to work in resource-limited settings, putting themselves at higher risk of contracting different blood borne infections, including HIV, a disease without cure so far. Thus the findings reflect the need for the in-service awareness program and the integration of content in the pre-service curriculum on PEP of HIV for the nurses who are at risk for occupational exposure.